Discovery of novel 1, 2, 4‐triazole phenylalanine derivatives targeting an unexplored region within the interprotomer pocket of the HIV capsid protein. Issue 12 (18th August 2022) - Jiang, Xiangyi; Sharma, Prem Prakash; Rathi, Brijesh; Ji, Xiangkai; Hu, Lide; Gao, Zhen; Kang, Dongwei; Wang, Zhao; Xie, Minghui; Xu, Shujing; Zhang, Xujie; De Clercq, Erik; et al.
Abstract: Human immunodeficiency virus (HIV) capsid (CA) protein is a promising target for developing novel anti‐HIV drugs. Starting from highly anticipated CA inhibitors PF‐74, we used scaffold hopping strategy to design a series of novel 1, 2, 4‐triazole phenylalanine derivatives by targeting an unexplored region composed of residues 106–109 in HIV‐1 CA hexamer. Compound d19 displayed excellent antiretroviral potency against HIV‐1 and HIV‐2 strains with EC50 values of 0.59 and 2.69 µM, respectively. Additionally, we show via surface plasmon resonance (SPR) spectrometry that d19 preferentially interacts with the hexameric form of CA, with a significantly improved hexamer/monomer specificity ratio (ratio = 59) than PF‐74 (ratio = 21). Moreover, we show via SPR that d19 competes with CPSF‐6 for binding to CA hexamers with IC50 value of 33.4 nM. Like PF‐74, d19 inhibits the replication of HIV‐1 NL4.3 pseudo typed virus in both early and late stages. In addition, molecular docking and molecular dynamics simulations provide binding mode information of d19 to HIV‐1 CA and rationale for improved affinity and potency over PF‐74 . Overall, the lead compound d19 displays a distinct chemotype form PF‐74, improved CA affinity, and anti‐HIV potency.